Changes in Canadian contraceptive choices: results of a national survey on hormonal contraceptive use - Allison J. Campbell; Victoria E. Claydon; Sarah Liva; Anita T. Cote (BMC Women's Health)
Abstract Background Since the introduction of the birth control pill in 1960, Canadians have been offered a number of different options for hormonal contraceptives, yet oral contraceptives remain the most popular methods. Research from other countries indicates this may be shifting, but the last comprehensive survey of Canadian hormonal contraceptive usage was published in 2009. Therefore, the aim of this study was to determine current hormonal contraceptive usage among pre-menopausal Canadians. Methods An online survey was distributed to pre-menopausal females aged 19–49 years via a third-party survey company. The survey included questions on respondents’ demographics and current and past hormonal contraceptive use. Prevalence of current hormonal contraceptive use was calculated by age. Chi-squared tests were conducted to determine whether there was an association between contraceptive choice and various demographic categories. Results Responses of 2306 female Canadians (age 33.4 ± 8.1 years) were analyzed and 29% of these respondents were currently using hormonal contraceptives. The most common choices were oral contraceptives (56.4%) and intrauterine device (IUD) (28.4%). Over 30% of hormonal contraceptive users were currently using a long-acting reversible contraceptive method. Conclusions These findings demonstrate a change in hormonal contraception use, notably an increase in the use of hormonal IUDs from 4 to 28% among Canadian hormonal contraceptive users over the last 15 years. This study also shows a high prevalence of alternative contraceptive options that may influence hormone levels differently than oral forms.